Catherine the Great Authors Her Empire - Kelsey Rubin-Detlev (Вивліоѳика, 2024)
Review of: Vera Proskurina, The Imperial Script of Catherine the Great: Governing with the Literary Pen, Boston: Academic Studies Press, 2023